Inclusion and Economic Independence of the Disabled Community - Waldan, Raziki; Widiati, Ari (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article explores the results of a service to the disabled community in Singkawang City, focusing on improving their economic inclusion and independence through mentoring in sharia e-commerce platforms. Using the Participatory Action Research (PAR) method, the difable community was actively involved in all stages, from problem identification through group discussions and interviews, to joint programme planning that determined training topics, activity schedules, and methods that suited their needs. The mentoring is conducted in a participatory manner through a series of training and sharia e-commerce practices, with the disabled community actively involved in every stage, including discussions, simulations, and hands-on practice. Programme evaluation was conducted with them, allowing for the integration of feedback to reflect on programme outcomes and improve future activities. The results recorded significant improvements in understanding and skills in using Islamic e-commerce platforms, increased market access for disabled products, and improvements in their economic independence. This article highlights the importance of participatory approaches and the utilisation of Islamic technology in empowering the disabled community towards sustainable economic inclusion.